Mali durumu bozulan aracı kurumlarda alınacak tedbirler ve özellikle tedrici tasfiye - Tevetoğlu, Mete (My University, 2005)
The subject of Capital Markets Law is to regulate and control the secure, transparent and stable functioning of the capital market and to protect the rights and benefits of investors with the purpose of ensuring an efficient and widespread participation by the public in the development of the economy through investing savings in the securities market. The intermediary institutions are auxiliary formation of the capital markets. Financial situation of intermediary institutions have important effects on the system. Therefore, the criterion of intermediary institutions which are in a financial breakdown are different than other corporations. Capital Markets Board is authorized to request the strengthening of the financial situations within a suitable period that shall be given in case it is determined that the financial structure of a intermediary institution has become weakened significantly; to restrict or remove the signature authorities of the employees of such institution; to take the needed measures in case it is determined that the needed measures are not taken by these institutions within this period that is given or their financial situations have become weakened to the extent that they shall not be able to meet their commitments, to stop temporarily the operations of these institutions without giving any period of time or to stop them permanently and remove their authorities; to make a decision for gradual liquidations in case these measures do not produce results and to request direct bankruptcy without gradual liquidation or when needed following the conclusion of liquidation. A decision may be made by the Board for the gradual liquidation of intermediary institutions, the authorities of which have been removed in accordance with subparagraph (h) of the first paragraph of Article 46 of Capital Market Law. The liquidation operations of these institutions shall be carried out by the Investors' Protection Fund. The objective of gradual liquidation is to liquidate the cash payments and the delivery obligations of capital market instruments to the customers due to the capital market operations carried out in the framework of the Law by setting aside the amount obtained by transforming the assets to in kind or cash according to their attributes. In the decision and operations of gradual liquidation, the provisions related to liquidation in the Turkish Commercial Code, the Execution and Bankruptcy Law and the other legislation shall not be applied. After a decision is made for gradual liquidation, the duties and authorities of the legal organs of the intermediary institutions shall be carried out by the Fund until the liquidation is concluded. A decision may be made by the Board to transfer to another institution the management of portfolios that are managed by an intermediary institution, including mutual funds and investment company portfolios. Payments by the intermediary institution for which a gradual liquidation decision is made shall be stopped and as of the date of this decision all its assets may be used only by the Fund. The Fund shall determine the assets and liabilities of the intermediary institution. The cash debts in the scope of the obligations that should be liquidated shall be calculated over the total principal capital and accrued interests at the date of the decision of gradual liquidation; with respect to the obligation to deliver capital market instruments, in cases where it cannot be delivered in kind, the debt shall be calculated based on the market value on the date the delivery went into default otherwise the day that the decision is made for gradual liquidation. The rights and obligations arising from contracts with maturity dates after the date of the decision for the gradual liquidation of the intermediary institution shall be determined as of their maturity dates. For the intermediary institutions which are not subject to gradual liquidation but for which a decision of bankruptcy has been made, payment shall be made from the Fund, with the approval of the Fund management, to the creditors for cash and shares arising from the share transactions on the list by considering the amounts owed which appear on this list. At the beginning of the gradual liquidation, first of all the capital market instruments shall be distributed to the holders of the rights in the customer settlement accounts. If the assets of the intermediary institution are not sufficient to meet the receivables of the holders of rights in the scope of the objective of liquidation, the payments made from the Fund and the liquidation expenses, then the Fund, with the concurrence of the Board, may request the bankruptcy of the intermediary institution.

Sermaye Piyasası Hukukunun konusu, tasarrufların menkul kıymetlere yatırılarak halkın iktisadi kalkınmaya etkin ve yaygın bir şekilde katılmasını sağlamak amacıyla; sermaye piyasasının güven, açıklık ve kararlılık içinde çalışmasını, tasarruf sahiplerinin hak ve yararlarının korunmasını, düzenlemek ve denetlemektir. Aracı kurumlar sermaye piyasasının yardımcı kuruluşlarıdır. Aracı kurumların mali durumu sistem üzerinde önemli etkilere sahiptir. Bu nedenle, aracı kurumların mali durumunun bozulması kriterleri diğer şirketlere göre faklıdır. Sermaye Piyasası Kurulu, sermaye piyasası kurumlarının, mali yapılarının ciddi surette zayıflamakta olduğunun tespiti halinde; verilecek uygun süre içinde, mali durumlarının güçlendirilmesini istemeye; kurum görevlilerinin imza yetkilerini sınırlandırmaya veya kaldırmaya; verilen bu süre içinde, bu kurumlar tarafından gerekli tedbirlerin alınmaması halinde veya mali durumlarının taahhütlerini karşılayamayacak kadar zayıflamış olduğunun tespiti halinde gerekli tedbirleri almaya, herhangi bir süre vermeksizin kurumların faaliyetlerini geçici olarak durdurmaya veya sürekli olarak durdurarak yetkilerini kaldırmaya; bu tedbirlerden netice alınmadığı takdirde tedrici tasfiyelerine karar vermeye ve tasfiyenin bitmesini takiben gerektiğinde veya tedrici tasfiyeye gitmeksizin doğrudan iflaslarını istemeye yetkilidir. SerPK m. 46 hükmünün 1. fıkrasının (h) bendi uyarınca yetkileri kaldıran aracı kurumların tedrici tasfiyelerine Kurul tarafından karar verilebilir. Bu kurumların tasfiye işlemleri ise Yatırımcıları Koruma Fonu tarafından yürütülür. Tedrici tasfiyenin hedefi, aracı kurumların malvarlığını durumun gereklerine göre aynen veya nakde çevirmek suretiyle elde edilen bedeli tahsis ederek, Kanun çerçevesinde yaptıkları sermaye piyasası faaliyetleri nedeniyle müşterilerine karşı olan nakit ödeme ve sermaye piyasası araçları teslim yükümlülüklerini tasfiye etmektir. Belirtelim ki, tedrici tasfiye karar ve işlemlerinde Türk Ticaret Kanunu, İcra ve İflas Kanunu ve diğer mevzuatın tasfiye ile ilgili hükümleri uygulanmaz. Tedrici tasfiye kararından sonra, aracı kurumun yasal organlarının görev ve yetkileri, tasfiye sonuçlanıncaya kadar Fon tarafından yerine getirilir. Aracı kurumun yönettiği, yatırım fonu ve yatırım ortaklığı portföyleri dahil, portföylerin yönetiminin, bir başka kuruluşa devrine de Kurulca karar verilmesi mümkündür. Tedrici tasfiye kararı üzerine ilgili aracı kurumun ödemeleri durur ve tüm mal varlığı üzerinde, bu karar tarihi itibariyle ancak Fon tasarruf edebilecektir. Aracı kurumun aktif ve pasifini de Fon tespit eder. Aracı kurumun, tasfiye kapsamında yer alan yükümlülüklerinden, nakit borçları, tedrici tasfiye kararının verildiği tarihteki ana para ve işlemiş faizleri toplamı üzerinden; sermaye piyasası aracı teslim borçları ise, aynen teslimin yapılamayacağı hallerde, varsa teslimde temerrüde düşülen tarihteki, aksi halde tedrici tasfiye kararının verildiği gündeki piyasa değeri itibariyle bulunacak nakit değerleri üzerinden hesaplanır. Aracı kurumun tedrici tasfiye kararının verilmesinden sonra vadesi gelen sözleşmelerinden doğan hak ve borçları da, vadeleri itibariyle belirlenmektedir. Tedrici tasfiyeye tabi tutulmayan ve haklarında iflas kararı verilen aracı kurumların, sıra cetvelinde yer alan hisse senedi işlemlerinden doğan nakit ve hisse senedi alacaklılarına, Fondan, Fon yönetiminin onayı ile bu cetvelde görünen alacak tutarları gözetilerek ödeme yapılır. Tedrici tasfiyenin başlangıcında, öncelikle müşteri saklama hesaplarındaki sermaye piyasası araçları hak sahiplerine dağıtılmaktadır. Aracı kurumun aktifleri, tasfiyenin amacı kapsamındaki hak sahiplerinin alacaklarını, Fondan yapılan ödemeleri ve tasfiye giderlerini karşılamaya yetmezse, Fon, Kurulun uygun görüşüyle aracı kurumun iflasını mahkemeden isteyebilecektir.
Keywords: Aracı Kurumlar; Hukuk; Özel Hukuk